Examining the role of brand value congruence, dimensions of brand experience in the influence of customer-brand identification on tourism brand productivity - Naser Seifollahi; Adeleh Dehghani Ghahnavieh (International Journal of Business and Development Studies, 2024)
Objective:Examining brand experience, value congruence,and customer engagement for tourism brand productivity.Given the significant effects that brand productivity in the tourism industry can have on a country's prosperity and economic progress, the primary objective of this research is to develop and empirically examine a conceptual model that elucidates the complex relationships among brand experience dimensions,brand value congruence, customer-brand identification, and brand productivity.Furthermore, the study investigates the moderating role of customer-brand engagement within this framework.Methods:The statistical population for this research comprises the tourists visiting the city of Isfahan.Given that the population is unlimited, a sample size of 400 participants was selected based on Cochran's formula, and the sampling method used was convenience sampling.The data was collected through a structured questionnaire.First, the validity and reliability of the measurement scales were assessed. Content validity and convergent validity were established, and the reliability was confirmed through Cronbach's alpha and composite reliability calculations. The results of these assessments were satisfactory. For data analysis, the researchers employed structural equation modeling techniques, utilizing SPSS25 and SmartPLS3.0 software.Results: Sensory experience, effective experience, behavioral experience, intellectual experience and brand value congruence have a positive and significant effect on customer-brand identification.Customer-brand identification has a positive and significant effect on brand productivity.customer-rand engagement can moderate the effect of brand-customer value congruence on customer-brand identification.Conclusions:The results of this research will help the authorities to promote and improve brand productivity in the tourism industry by focusing on customer-brand engagement, brand value congruence and customer-brand identification,and considering different dimensions of customer experiences.